Removal of Methylene Blue from Aqueous Solutions by Waste Paper Derived Activated Carbon - Mohammad Ali Baghapour; Babak Djahed; Mojdeh Ranjbar (Shiraz University of Medical Sciences, 2013)
Background and Objectives: Activated carbon is an adsorbent which is mostly employed in order to remove dye from aqueous solutions; however, commercial activated carbon is expensive and this is considered as an obstacle for its usage. Therefore, the present study aimed to use waste paper as an inexpensive precursor to produce activated carbon. Materials and Methods: In the present study, KOH was used for the chemical activation process; in order to prevent the precursor oxidation during the carbonization process, a completely sealed furnace was used. In order to determine the characteristics of the prepared activated carbon texture, N2 gas adsorption and BET isotherm were used. Moreover, Langmuir, Freundlich, Temkin, and Redlich-Peterson isotherm models as well as Pseudo-first order, Pseudo-second order, and intra-particle diffusion kinetic models were used to determine the characteristics of Methylene Blue adsorption on the prepared adsorbent. Results: According to the results, SBET and VTOTAL were 66.01m2/g and 0.063cc/g, respectively. Ferudlich and pseudo-second order models were the best isotherm and kinetic models for prediction of the Methylene Blue adsorption on the produced adsorbent. Furthermore, the qmax constant from the Langmuir model was obtained as 68.03 mg/g. Conclusion: In comparison to other studies, the produced activated carbon in the present study had a desirable surface area and adsorptive capacity for methylene blue adsorption in aquatic environments. Moreover, it seems that preparing activated carbon from waste newspaper is inexpensive, effective, and environment friendly.